PERUBAHAN SIFAT KIMIA TANAH SETELAH APLIKASI TANDAN KOSONG KELAPA SAWIT PADA DUA KELAS TEKSTUR TANAH - Putri Winda Asih; Sri Rahayu Utami; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2019)
The increase production of oil palm plantation is followed by the residue from processing palm oil mill effluent (POME) and oil palm empty fruit bunches (EFB). The POME is widely applied in oil palm plantation, whereas EFB is limited used. This study aimed to determine the effect of EFB application on soil chemical properties in Ultisol. This study was conducted in the Soil Chemical and Biological Laboratories, Agriculture Faculty, Brawijaya University Malang. Soil samples were collected from Batanghari and Sarolangun regencies, Jambi Province. This study was designed using randomized complete design with 6 treatments, including clay loam Ultisol (CLU) + EFB (T1B1); CLU + palm oil fibre (T1B2); CLU + EFB + fibre (T1B3); sandy loam Ultisol (SLU) + EFB (T2B1); SLU + fibre (T2B2); SLU + EFB + fibre (T2B3), and 3 replicates. The results showed that application oil palm residues (e.g EFB and fibre) increased soil organic C, available K, total N, and CEC on clay loam Ultisol with the highest increase was observed at the T1B3 (CLU + EFB + fibre) for 12 weeks incubation. This study summarized that oil palm residues can potentially be used as organic fertilizer in oil palm plantation.